Assessment of Multi-Depth Water Quality Dynamics in an Artificial Lake: A Case Study of the Ribnica Reservoir in Serbia - Dragana Milijašević Joksimović; Dejana Jakovljević; Dejan Doljak (Applied Sciences)
High water quality in reservoirs used for drinking water supply and located within protected areas is of crucial importance for sustainable water-resource management. This study aims to evaluate the multi-depth water quality dynamics of the Ribnica Reservoir in western Serbia, combining two standardized assessment tools: the Serbian Water Quality Index (SWQI) and the Canadian Water Quality Index (CWQI). Data collected at various depths during 2021 and 2022 were analyzed to assess physico-chemical parameters and their impact on water quality, while the absence of microbiological data was noted as a limitation affecting the comprehensiveness of the assessment. The SWQI results indicated a general improvement in water quality over time, with values ranging from medium (82) to excellent (95) in 2021 and increasing from good (89) to excellent (98) in 2022. In contrast, the CWQI revealed specific risks, notably elevated concentrations of aluminum, mercury, and chromium, and reduced dissolved oxygen levels, with overall CWQI values ranging from poor (40) to good (88) depending on depth and parameter variability. The study highlights the necessity for continuous, comprehensive monitoring, including microbiological analyses and seasonal assessments, both within the reservoir and in the Crni Rzav River and its tributaries, to better understand pollutant sources and catchment influences. Strengthening microbiological and heavy metal monitoring, along with implementing proactive management strategies, is essential for preserving the Ribnica Reservoir’s ecological integrity and securing its long-term role in drinking water provision.